2023
DOI: 10.1038/s41598-023-34059-1
|View full text |Cite
|
Sign up to set email alerts
|

Mito-nuclear discordance within Anthozoa, with notes on unique properties of their mitochondrial genomes

Abstract: Whole mitochondrial genomes are often used in phylogenetic reconstruction. However, discordant patterns in species relationships between mitochondrial and nuclear phylogenies are commonly observed. Within Anthozoa (Phylum Cnidaria), mitochondrial (mt)-nuclear discordance has not yet been examined using a large and comparable dataset. Here, we used data obtained from target-capture enrichment sequencing to assemble and annotate mt genomes and reconstruct phylogenies for comparisons to phylogenies inferred from … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 85 publications
(142 reference statements)
6
18
0
Order By: Relevance
“…The four transcriptomic phylogenies generated here (Fig. 2, S2-4) recovered all sampled hexacoral lineages (i.e., Scleractinia, Corallimorpharia, Actiniaria, Zoantharia, Ceriantharia) as monophyletic and found Scleractinia and A Cnidarian Phylogenomic Tree Fitted With Hundreds of 18S Leaves Corallimorpharia as sister taxa (discussed further below), concurring with many recent phylogenomic studies (Kayal et al, 2018;Quattrini et al, 2017Quattrini et al, , 2020Quattrini et al, , 2023Zapata et al, 2015). In the 18S tree, Zoantharia was non-monophyletic with a sample labeled as Zoanthus falling out among the Antipatharia; we suspect that this is a contaminant or mislabeled sequence rather than evidence for zoantharian polyphyly.…”
Section: Hexacoralliasupporting
confidence: 88%
See 1 more Smart Citation
“…The four transcriptomic phylogenies generated here (Fig. 2, S2-4) recovered all sampled hexacoral lineages (i.e., Scleractinia, Corallimorpharia, Actiniaria, Zoantharia, Ceriantharia) as monophyletic and found Scleractinia and A Cnidarian Phylogenomic Tree Fitted With Hundreds of 18S Leaves Corallimorpharia as sister taxa (discussed further below), concurring with many recent phylogenomic studies (Kayal et al, 2018;Quattrini et al, 2017Quattrini et al, , 2020Quattrini et al, , 2023Zapata et al, 2015). In the 18S tree, Zoantharia was non-monophyletic with a sample labeled as Zoanthus falling out among the Antipatharia; we suspect that this is a contaminant or mislabeled sequence rather than evidence for zoantharian polyphyly.…”
Section: Hexacoralliasupporting
confidence: 88%
“…Columns labeled D2024-18S and D2024-Tr indicate the 18S and transcriptomic datasets generated in this study, respectively. The other studies included are Chang et al, 2015;Kayal et al, 2018;Quattrini et al, 2017Quattrini et al, , 2020Quattrini et al, , 2023Zapata et al, 2015, andStampar et al, 2019. (GCF_000090795), the placozoan Trichoplax adhaerens (ABGP00000000), the fruit fly Drosophila melanogaster (GCF_000001215), the marine annelid Capitella teleta (PR-JNA175705), the limpet Lottia gigantea (PRJNA175706), the purple sea urchin Strongylocentrotus purpuratus (https://metazoa.ensembl.org, release 47), and the zebra finch Taeniopygia guttata (ABQF00000000) (Table S3). We used diamond v0.9.…”
Section: Phylogenomic Matrix Construction and Phylogeny Estimationmentioning
confidence: 99%
“…By building a new conserved element phylogeny with an almost identical taxon set to the complete mitochondrial genome phylogeny, we provide evidence that differences are due to mitonuclear discordance and not insu cient or uneven taxon sampling. Mitonuclear discordance has been previously reported across deep to shallow divergences within Anthozoa (Quattrini et al 2023b). This is the rst time mitonuclear discordance has been reported within the family Keratoisididae.…”
Section: Phylogeny and Mitonuclear Discordancementioning
confidence: 69%
“…However, the presence of discordance between mitochondrial and nuclear inferences provides evidence that concatenating sequences of nuclear and mitochondrial origin is inappropriate within Keratoisididae. Interfamilial studies using both nuclear and mitochondrial genomes have also found mitonuclear discordance at the familial rank within Anthozoa (Quattrini et al 2023b). Therefore, until more studies investigate within familial relationships, caution should be applied when making phylogenetic inferences inside any anthozoan family.…”
Section: Phylogeny and Mitonuclear Discordancementioning
confidence: 99%
See 1 more Smart Citation